Anosmia as an adverse effect of dorzolamid - Turgut, Burak; Turkcuoglu, Peykan; Guler, Mete; Akyol, Nuray; Celiker, Ulku; Demir, Tamer (Blackwell Publishing, 2007)
[Abstract Not Available]
Keywords: Carbonic-Anhydrase